Resistance to Tospoviruses in Vegetable Crops: Epidemiological and Molecular Aspects - Turina, Massimo; Kormelink, Richard; Resende, Renato O (Annual review of phytopathology, 2016)
During the past three decades, the economic impact of tospoviruses has increased, causing high yield losses in a variety of crops and ornamentals. Owing to the difficulty in combating thrips vectors with insecticides, the best way to limit/prevent tospovirus-induced diseases involves a management strategy that includes virus resistance. This review briefly presents current tospovirus taxonomy, diversity, molecular biology, and cytopathology as an introduction to a more extensive description of the two main resistance genes employed against tospoviruses: the Sw5 gene in tomato and the Tsw in pepper. Natural and experimental resistance-breaking (RB) isolates allowed the identification of the viral avirulence protein triggering each of the two resistance gene products; epidemiology of RB isolates is discussed to reinforce the need for allelic variants and the need to search for new/alternative resistance genes. Ongoing efforts for alternative resistance strategies are described not only for Tomato spotted wilt virus (TSWV) in pepper and tomato but also for other vegetable crops heavily impacted by tospoviruses.